Prospects for the Development and Improvement of the Content by the Art Teaching and Art Therapy Work in Kazakhstan (Journal of Educational Sciences, 2017)
The article presents the results of forecasting the development and direction of improving the content of art teaching and art therapy work in the Republic of Kazakhstan. Analysis of publications suggests that a unified understanding of art pedagogy and art therapy is not yet generated, in the publications of recent years there are phrases such as: «art therapy pedagogy and psycho-pedagogy art», «art pedagogical technology», «art pedagogical approach», etc. Based on the analysis of literature several types of prediction are highlighted. Foundation of art therapy with its expression, communication, symbolization, with an action which involves artistic creativity); applied forecasting (where the process of creation); the pedagogical forecast (increase of the role of art therapists in education); psychological projection (development and improvement of the «language» of visual and plastic expression). Proposed map of the ways of improving the content of art teaching and art therapy work-for example, implemented in the Republic of Kazakhstan art teaching and art therapy services in Kazakhstan.Key words: art therapy, art education, art teaching, art therapy work, therapy, intermodal expressive arts, music therapy, dance-movement therapy, drama therapy, art-pedagogical activity.